Challenges Faced By Novice Teachers: A Qualitative Analysis - İshak Kozikoğlu; Nuray Senemoğlu (Anı Publishing, 2018)
The purpose of this study is to determine the challenges faced by novice teachers in their first year of profession. This research was conducted with 33 novice teachers working in Istanbul, Konya, Gaziantep and Van provinces. Research data were obtained using semi-structured interview form developed by the researchers. In the analysis of the data, descriptive analysis and content analysis techniques were used. As a result of the research, it was found that the novice teachers faced various challenges in teaching planning and implementation, classroom management, relations with society and adaptation to the physical environment, relations with colleagues, administrators, parents, and mentor teachers and the lack of physical infrastructure of the school in the first year of the profession. Existing pre-service teacher education and induction programs should be revised taking into account the challenges that novice teachers most frequently encounter during the first year of the profession.